Customer Relationship Management (CRM) in Context of Food Marketing - A Fuzzy Logic Approach - Mishra, Devesh; Deb, Madhurima; Guin, Kalyan Kumar; Sinha, Gautam (Indian Journal of Marketing, 2007)
The most successful brands on earth connect with their consumers emotionally in addition to logical facts and rational appeals. Effective food product marketers connect with concerned and aware consumers willing to pay a premium to buy food products by empowering them to clean the air, purify the water, or help save endangered forests and species. As society becomes more concerned with the natural environment, businesses have begun to modify their behavior in an attempt to address society’s "new" concerns. Some businesses have been quick to accept concepts like environmental management systems and waste minimization, and have integrated environmental issues into all organizational activities The present paper aims at ranking the various variables that lead to purchase, the paper also tries to show how Customer Relationship Management (CRM) can lead to the success of food marketing considering execution of Food Marketing as the prime responsibility of the marketer.